PENDIDIKAN KARAKTER DALAM KAJIAN TEORI EKOLOGI PERKEMBANGAN - Yuliawan, Dhedhy; Taryatman, Taryatman (Universitas Sarjanawiyata Tamansiswa, 2020)
The development of the era can no longer be denied. When technology develops, it changes the character of children. The problem reflected reflects the application of this indicator as to the character of education in Indonesia. Character education has not been approved successfully by looking at agreeing to the problem above. This makes character education meaningful and important to do in the family and the community. Problems that occur in children today can not be denied anymore given the facts that occur reflect changes in the child's character. Through ecological theory, character development can be instilled through interactions within subsystems. This theory provides a study of the interrelationships between children and families, between children and peers, between children with the school environment, and between children and society. Through this theory can also be presented as an understanding of the interaction between dynamic and complex individuals. Thus character education can be instilled using developmental ecology theory discussed in each subsystem, namely microsystems, ecosystems, macrosystems, and ecosystems. Each subsystem provides a difference in the character of children with the interaction of family, school, community.